A Ka-band fourth-order SIW filter power divider with wide out-of-band suppression. (March 2023) - Fan, Chenhui; Liu, Xiaoxian; Liu, Nuo; Yang, Yintang
Abstract: In this paper, a Ka-band fourth-order substrate integrate waveguide (SIW) filter power divider (FPD) based on the quartz glass substrate is presented. The excitation becomes electrical through the coupling position of the input and output feeders, and the parasitic passband produced by the even-order mode is suppressed consequently. Different size of the resonant cavity is proposed for the resonance and transmission of the signal at the same frequency to eliminate higher order mode and generate two transmission zeros (TZs) at 34.14 GHz and 36.64 GHz respectively. An S-type coupling slot is exploited to realize the electronic coupling between the resonate cavities. The measurement and simulation stop band achieve 3.1 f 0 (limited by test conditions) and above 8 f 0 in −20 dB, respectively. Good agreement is achieved between the measured results and the simulated ones.